TO IMPROVE THE QUALITY OF LEARNING TEACHERS USING FRIENDLY SUPERVISION - Hiliyati Yus (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Friendly supervision conducted by principals is basically an effort to improve the quality of education and teaching in schools with core teaching programs supported by other elements such as teachers, facilities and infrastructure, curriculum, teaching and assessment systems. This research method is a school action research study subject of three teachers in class VI with the results of the study seen in the completeness of the administration of learning owned by teachers in the first cycle the average value is 66 with less categories, while the completeness of the administration of learning owned by teachers in the second cycle average the average value is 87 with a very good category. In the implementation of learning activities carried out by teachers in the first cycle the average value was 77.33 with enough categories, increasing in the second cycle with an average value of 90 with good categories. It was concluded that friendly supervision was effectively carried out in improving the quality of teacher learning.